Encountering Vulnerabilities through 'Filmmaking for Fieldwork'. (June 2015) - Barabantseva, Elena; Lawrence, Andy
In this article we discuss the potential of observational and participatory filmmaking methods to both explore and represent a research subject through a documentary film. We position our project 'British Born Chinese' about the experiences of the second generation of Chinese migrants in relation to other recent audio-visual interventions in IR, and present our methodological approach of observational and dialogical engagement with participants and the ethics of representation related to it. In doing this, we explore the potential of audio-visual research to go beyond identity-based forms of inquiries concerning, in particular, migrant and diasporic experiences. Our aim is to develop a situated and contextualised understanding of how and under what conditions individuals resort to racialised forms of belonging. We consider the promise and limitations of observational filmmaking to depart from the structures of representation to evoke alternative solidarities around vulnerability.